2010
DOI: 10.1039/b921665k
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of water, hydrogen and their mixtures with SnO2 based materials: the role of surface hydroxyl groups in detection mechanisms

Abstract: DRIFTS, TGA and resistance measurements have been used to study the mechanism of water and hydrogen interaction accompanied by a resistance change (sensor signal) of blank and Pd doped SnO(2). It was found that a highly hydroxylated surface of blank SnO(2) reacts with gases through bridging hydroxyl groups, whereas the Pd doped materials interact with hydrogen and water through bridging oxygen. In the case of blank SnO(2) the sensor signal maximum towards H(2) in dry air (R(0)/R(g)) is observed at approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 27 publications
3
62
0
Order By: Relevance
“…The lower vibrational wavenumber (3400−3200 cm −1 ) of OH···OH compared to isolated OH species (3640−3500 cm −1 ) mirrors the O−H bond loosening and strengthening of that of M−OH that is typical for rooted hydroxyls. 30 The reason for increased impact of OH···OH to the hydrated species of modified samples might be a larger concentration of rooted OH groups and/or their higher acidic nature, which for SnO 2 /PdO x agrees with TPD-NH 3 data. Noteworthy, with the FTIR patterns of modified samples looking similar, the OH surf and H 2 O surf absorption bands of SnO 2 /PdO x were more intense ( Figure 6).…”
Section: ■ Results and Discussionsupporting
confidence: 66%
“…The lower vibrational wavenumber (3400−3200 cm −1 ) of OH···OH compared to isolated OH species (3640−3500 cm −1 ) mirrors the O−H bond loosening and strengthening of that of M−OH that is typical for rooted hydroxyls. 30 The reason for increased impact of OH···OH to the hydrated species of modified samples might be a larger concentration of rooted OH groups and/or their higher acidic nature, which for SnO 2 /PdO x agrees with TPD-NH 3 data. Noteworthy, with the FTIR patterns of modified samples looking similar, the OH surf and H 2 O surf absorption bands of SnO 2 /PdO x were more intense ( Figure 6).…”
Section: ■ Results and Discussionsupporting
confidence: 66%
“…As shown in Figure 4b, we observed that humid aging enhanced the oxygen adsorption. Thus, an increase in the amount of oxygen on the surface by the humid aging facilitated the combustion of hydrogen, thereby suppressing the hydroxyl poisoning [16,17,18]. However, in high wet air (P H2O : 0.03 atm), the sensor response became less than S = 10.…”
Section: Resultsmentioning
confidence: 99%
“…Water vapor, which is always present in the atmosphere, has been recognized as the most harmful gas for semiconductor-type sensors because the adsorbed water blocks the oxygen adsorption on the surface (hydroxyl poisoning) [6,7,16,17,18]. The formation of hydroxyl groups on Sn 4+ sites can be expressed by the following equation [16]:H 2 O + O − ad (or O 2− ad ) + 2Sn → 2(Sn-OH) +e − (or 2e − ) …”
Section: Introductionmentioning
confidence: 99%
“…(Pavelko et al, 2010). While the effect of background water and oxygen species on gas sensing properties of SnO 2 materials has recently been reported (Korotcenkov et al, 2007;Großmann et al, 2013), this issue is still a subject of debate due to the complexity of this matter.…”
Section: Introductionmentioning
confidence: 99%